Upaya Memperkuat Hubungan Sosial Dalam Kehidupan Bermasyarakat - Hanafi, Arman; Yasin, Muhammad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2023)
This study aims to describe the concept of social relations and efforts to strengthen social relations in the midst of social life. The method used in this research is a qualitative method with a type of library research. The results showed that social relations are interactions and relationships between individuals or groups in society that involve the way people interact, influence each other, and form bonds with other people in their social environment. The efforts that can be made to strengthen social relations in the community are: Effective communication; Empathy and mutual understanding; Respect for diversity; Collaboration and partnership; and Active Participation. Strengthening social relationships takes patience, understanding, and a commitment to building positive bonds with others. By being actively involved and practicing the values of mutual respect and cooperation, we can strengthen social relations in society.